Pâturage régénératif and bonne gouvernance des parcours face au changement climatique - Nefzaoui, Ali; Rudiger, Udo; Hassan, Sawsan; Frija, Aymen; Ouerghemmi, Hassen; Shiri, Zahra; Louhaichi, Mounir (International Center for Agricultural Research in the Dry Areas, 2024)
This report summarizes the findings and discussions from the workshop on "Livestock and Climate: Regenerative Grazing and Good Governance of Pastures Facing Climate Change," held in September 2024. The workshop brought together 29 participants, including stakeholders from various Tunisian governorates, to address the challenges and opportunities in managing pastoral ecosystems in the face of climate change. Key objectives included reviewing the current state of pasture rest practices, proposing mechanisms for improving these procedures, and discussing the roles of professional organizations and regulatory authorities. Participants highlighted the importance of regenerative grazing techniques and emphasized the need for better governance and collaboration among stakeholders to enhance the sustainability of pastoral systems.